Defining and improving the role of emergency medical services in Cape Town, South Africa. Issue 8 (4th February 2016) - Anest, Trisha; Stewart de Ramirez, Sarah; Balhara, Kamna S; Hodkinson, Peter; Wallis, Lee; Hansoti, Bhakti
Abstract : Introduction: Low and middle income countries bear a disproportionate burden of paediatric morbidity and mortality. South Africa, a middle income country, has unacceptably high mortality in children less than 5 years of age. Many factors that contribute to the child mortality rate are time sensitive and require efficient access to emergency care. Delays and barriers within the emergency medical services (EMS) system increase paediatric morbidity and mortality from time sensitive illnesses. Methods: This study is a qualitative evaluation of the prehospital care system for paediatric patients in Cape Town, South Africa. A purposive sample of healthcare personnel within and interacting with the EMS system were interviewed. A structured interview form was used to gather data. All interviews were audio recorded and transcribed; two independent reviewers performed blinded content analysis of the transcribed script. Results: 33 structured interviews were conducted over a 4 week period. Eight broad themes were identified during coding, including: access, communication, community education, equipment, infrastructure, staffing, training and triage. Subcategories were used to identify areas for targeted intervention. Overall agreement between the two independent coders was 93.36%, with a κ coefficient of 0.69. Conclusions: The prehospital system is central to delivering time sensitive care for paediatric patients. In a single centre middle income setting, communication barriers between dispatch personnel and medical facilities/EMS personnel were deemed to be a high priority intervention in order to improve care delivery. Other areas for targeted interventions should include broadening the advanced life support provider base and introducing basic medical language in dispatch staff training.